The Microbiome and Blood Pressure: Can Microbes Regulate Our Blood Pressure? - Al Khodor, Souhaila; Reichert, Bernd; Shatat, Ibrahim F. (Frontiers in Pediatrics, 2017)
The surfaces of the human body are heavily populated by a highly diverse microbial ecosystem termed the microbiota. The largest and richest among these highly heterogeneous populations of microbes is the gut microbiota. The collection of microbes and their genes, called the microbiome, has been studied intensely through the past few years using novel metagenomics, metatranscriptomics and metabolomics approaches. This has enhanced our understanding of how the microbiome affects our metabolic, immunologic, neurologic and endocrine homeostasis. Hypertension is a leading cause of cardiovascular disease worldwide; it contributes to stroke, heart disease, kidney failure, premature death and disability. Recently, studies in humans and animals have shown that alterations in microbiota and its metabolites are associated with hypertension and atherosclerosis. In this review, we compile the recent findings and hypotheses describing the interplay between the microbiome and blood pressure, and we highlight some prospects by which utilization of microbiome-related techniques may be incorporated to better understand the pathophysiology and treatment of hypertension.